1987
DOI: 10.1271/bbb1961.51.399
|View full text |Cite
|
Sign up to set email alerts
|

Purification and some properties of raw starch-binding amylase of Clostridum butyricum T-7 isolated from mesophilic methane sludge.

Abstract: The raw starch-binding a-amylase of C. butyricum, an acidogenic anaerobe found in mesophilic methane sludge, was purified by chromatographyon a column ofBio-Rex 70 after the enzymehad been liberated from potato starch granules. The molecular weight of the purified enzyme was determined to be 89,000 by sodium dodecyl sulfate (SDS) disc electrophoresis.The iodine reaction completely disappeared at 9% hydrolysis of soluble starch by the enzyme, and the successive formation of maltooligosaccharides proceeded at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 1 publication
4
12
0
Order By: Relevance
“…4). The pH stability was similar to that of α‐amylase from Clostridium butyrium T‐7 (pH 5.5–7.5) 28 and tilapia β‐amylase (pH 5.5–7.5) 19 . The optimal pH of amylases seemed to be species‐dependent.…”
Section: Resultsmentioning
confidence: 55%
“…4). The pH stability was similar to that of α‐amylase from Clostridium butyrium T‐7 (pH 5.5–7.5) 28 and tilapia β‐amylase (pH 5.5–7.5) 19 . The optimal pH of amylases seemed to be species‐dependent.…”
Section: Resultsmentioning
confidence: 55%
“…Compared with other bacterial enzyme preparations the hydrolysis, especially of native potato starch, proceeds in an efficient way. In this respect we can mention B. circulans (Taniguchi et al 1982), B. subtilis (Hayashida et al 1988), C. butyricum (Tanaka et al 1987) or R. gelatinosa (Buranakarl et al 1988). Moreover, the activity ratio of N S D A over SSDA of the crude enzyme preparation is relatively high: hydrolysis of soluble starch proceeds only about seven times faster than hydrolysis of native potato starch.…”
Section: Discussion Referencesmentioning
confidence: 99%
“…Amylases have important applications in diverse industries such as baking, brewing, detergent, medicine, textile, paper and pharmaceutical (Kennedy, 1987). Extracellular amylase (Tani et al, 1986;Mahmoud, 1993) have been found in various species of fungi (Pandy et al, 2000;Jaffar et al, 1993;Norouzian and Jaffar, 1993;Frandsen et al, 1999;Reilly, 1999), bacteria (Srivastava and Baruah, 1986;Tanaka et al, 1987) and yeasts (Bui et al, 1996;Yamashita et al, 1987;Yamashita et al, 1985;Dohmen et al, 1990;Hostinova et al, 1991).…”
Section: Introductionmentioning
confidence: 99%